A profissionalidade dos(as) diretores(as) escolares em tempos de Nova Gestão Pública - Bertochi, Patrícia Ribeiro Tempesta (Universidade Federal de São Carlos, 2021)
The objective of this research was to investigate the process of construction of the professionality of principal teacher facing the complexity of the school and the growing role of the so-called New Public Management (NGP). With the democratization of access to education, the advances and setbacks in the teaching career, as changes in the social function of the school and pressures from neoliberal reformist policies and its managerial version of administration, the professionality of the principal teacher began to be built based on a new dynamic. In Brazil, in the 1990s, the NGP was instituted having the supposed professionalization of public servants as one of its principles. From this perspective, the professionalization of teaching takes on a new guise, using a neotechnicist rhetoric supported by concepts of competence, efficiency and effectiveness, depoliticizing as actions, materialized in an intensification of work (hyperbureaucratization) and in the loss of control over it, separating planners and executors, delegitimizing and disqualifying the performance of teaching professionals, giving rise to a process of proletarianization. This ideological bias turns professionals into salaried and bureaucratized specialists, subject to large bureaucratic associations. The repercussion of this process causes a great value load on teaching professionals, since they are responsible for the realization of the right to education. In the midst of this context, a research question is: How has the professionality of principal teacher been built? This role of principal is based on two principles: acting as a representative of the State and the school team, and acting as an advance representative in the institution. However, empirical studies on the principal teacher have not been done in light of the educational nature of this role. The director's graduation portrays an identity fragility, in addition to the lack of continued training. Professionality is a powerful concept in the understanding of the function, in opposition to the neotechnicist rhetoric of professionalization, as it encompasses other constituent elements of work: knowledge, ideology, attitude, epistemological and intellectual posture in relation to professional practice, skills, procedures, culture and psychological conditions. To investigate it, three data collection instruments were used: a questionnaire on the Pedagogical Work Schedule of Principals, in the context of which there was an episode of continuing education offered to principals of the researched education network; a semi-structured interview and an open interview. Data were analyzed in two moments. First, in the section that deals with advances and obstacles in the process of institution of the function, comparing studies on the effects of neoliberal reason and NGP in the function, with the perceptions that principals have about it. In a second moment, the analysis of four characteristics of the principals' professionality was carried out: competence, specificity of the function and of their knowledge, autonomy and belonging to a collective body. In the dimension of the function's specificity, a framework was elaborated with what we call nuances of the principals' professionality, namely: State representative (managerial and/or proletarianized action) and/or advanced pair. The analysis confirmed the hypothesis that the principals' professionality assumes a substrate composed of elements arising from the change in the exercise of their function, increasingly removed from its educational nature, making it difficult for the principal to have a more intellectual and critical performance.
The professionalitat of school principals in times of New Public Management
Keywords: Profissionalidade do diretor escolar; Função de Diretor Escolar; Formação para Diretor; Gestão escolar e Nova Gestão Pública; Políticas Educacionais; School principal's professionality; Role of Principal Teacher; Principal Teacher Training; School management and New Public Management; Educational Policies; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO